Wayang as Local Communication Media in Building Public Awareness of Environmental Crisis - Rachmad Kristiono Dwi Susilo; Agung Wijaya Kusuma; Agung Wibowo (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
A movement to conserve Gemulo water source conducted by FMPMA group uses cultural values through puppet performance (nanggap wayang) in Bulukerto, Bumiaji and Sidomulyo Villages, Batu City, East Java. Nanggap wayang is used to be a local communication media to inculcate environment conservation values, social movement, and development communication. This research used qualitative method and ethnographic approach aiming to analyze the role and contribution of leather puppet performance (nanggap wayang kulit) on the performance of Gemulo water source conservation movement initiated by FMPMA community and some related society elements. This research employed empirical findings and various literature review references in its analysis. The result of research shows that wayang is still capable of serving as local communication medium for modern community amid massive new media development. Wayang, as local communication medium, provides education, guidance, morality value, and Javanese symbol. The complexity of wayang function also represents collective behavior inculcating Javanese values. Philosophical story of very ecological wayang can enrich the right-on-target and sustainable conservation model. Wayang also becomes effective media of development communication, of change, of socialization, and of education, thereby triggering the development of consciousness and positive feedback from local people (community).